Graphene oxide treatment method for preparing graphene oxide concrete
The mixture of the alcohol graphene and the surface active agent through ultrasonic oxygenhene, and saved at low temperature conditions, solved the problem of reunion caused by long -term storage in batch production, realized the stability and performance of gallery oxide concrete concrete Excellent effect.
Patent Information
- Application Number
- CN202411434723.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to effectively solve the agglomeration problem caused by long-term storage during mass production and transportation, resulting in uneven distribution in concrete and degradation of performance.
Ultrasonic decentralized oxygenhene and polycarboxylic acid hydraulic agent, non -meal acid, sodium phenylphenylsulfonate and other surfactants such as hybrid fluid, and keep it refrigerated at low temperature conditions to ensure that the oxygenne gramne is maintained within a certain period of time. Good dispersion state.
Through this method, after 7 days of preservation, the oxide can still effectively improve the compressive strength, tensile strength and other performance indicators of concrete to ensure excellent stability and performance of vita -graphene concrete.
Smart Images

Figure BDA0005084619980000021 
Figure BDA0005084619980000022 
Figure FDA0005084619970000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a method for processing and preserving graphene oxide before large-scale production of graphene oxide concrete. Background Art
[0002] Graphene oxide (GO) is a single carbon atom layer with a regular hexagonal flaky crystal structure and oxygen-containing functional groups such as hydroxyl and carboxyl. Graphene oxide can extend to several microns to tens of microns in lateral dimensions, and its structure is close to a plane and presents a two-dimensional network.
[0003] When graphene oxide is added to concrete, it affects the hydration reaction of cement. The addition of graphene oxide increases the yield of hydrated calcium silicate in concrete, promotes the formation and arrangement of cement hydration crystals, improves the structure of the cement stone and aggregate interface, reduces porosity, and increases density. While improving the microstructure, graphene oxide can also improve the compressive strength, tensile strength, impermeability, resistance to chloride ion erosion, carbonization resistance, and freeze-thaw resistance of concrete.
[0004] At present, the research on the preparation of graphene oxide concrete is mainly aimed at small-batch production in the laboratory, and less attention is paid to the problems in mass production. In actual use scenarios, due to the high requirements for technology and equipment for the batch preparation of graphene oxide, it can only be transported to the site of use by purchasing or producing graphene oxide dispersion in a different location. The long-term storage of graphene oxide dispersion will cause the graphene oxide to aggregate into larger clumps, a phenomenon called agglomeration. After the agglomerated graphene oxide is added to concrete, it is unevenly distributed in the concrete, resulting in a large number of pores in the local area, causing the performance of the concrete to deteriorate. Summary of the invention
[0005] The object of the present invention is to provide a graphene oxide processing method for preparing graphene oxide concrete, characterized in that it comprises the following steps:
[0006] (1) Prepare the water reducing agent: Place the water reducing agent and water in a reactor and mix them.
[0007] (2) Sodium dodecylbenzene sulfonate and gallic acid are placed in a reactor and stirred to obtain a mixed solution A.
[0008] (3) The graphene oxide dispersion liquid is mixed with the mixed solution A, and stirred to obtain a mixed solution B. The mixed solution B is ultrasonically dispersed to obtain a mixed solution C.
[0009] (4) Immediately pour the mixed solution C into a light-proof container and refrigerate.
[0010] (5) Prepare a mixture D of water and water reducing agent before mixing concrete.
[0011] (6) Pour the dry concrete into the mixer and stir at low speed until the dry concrete is evenly mixed.
[0012] (7) Adding the mixed solution C and the mixed solution D to the dry material stirred uniformly in step (6) at the same time, and the mixed solution C and the mixed solution D are not mixed before being added to the dry material.
[0013] (8) Stirring the mixed system of step (7) until it is fully stirred to obtain concrete for pouring.
[0014] The invention relates to a graphene oxide treatment method for preparing graphene oxide concrete-1-by mixing graphene oxide with polycarboxylate water reducer, gallic acid and dodecane.
[0015] After mixing with surfactants such as sodium benzene sulfonate, ultrasonic dispersion and low-temperature storage are carried out to ensure that the graphene oxide can still meet the requirements for preparing graphene oxide concrete after being stored for a certain period of time, which is beneficial to the mass production and promotion of graphene oxide concrete.
[0016] Further, the mass ratio of mixed solution B is:
[0017]
[0018] Further, the mass ratio of the mixed solution D is:
[0019] 200 to 450 parts water
[0020] 8 to 16 parts of water reducing agent.
[0021] In step (7), the prepared mixed solution C and mixed solution D are used in a ratio of 1:1. Further, when the mixed solution C and mixed solution D are added with dry materials to prepare concrete, the water-binder ratio of the concrete is 0.18 to 0.21.
[0022] Furthermore, the mass ratio of the water reducing agent used in step (1) to the graphene oxide dispersion used in step (3) is 1:3-4.
[0023] Furthermore, the mass ratio of the water used in step (1) to the graphene oxide dispersion used in step (3) is 3 to 4:1.
[0024] Furthermore, the solid content of the graphene oxide dispersion is 0.005 wt% to 0.01 wt%, the graphene oxide has a diameter of 1 μm to 7 μm, a carbon content of 50% to 56%, and an oxygen content of 42% to 48%.
[0025] Furthermore, in step (3), the mixed solution A is stirred evenly for 1 to 2 minutes to obtain a mixed solution B.
[0026] Furthermore, in step (3), the mixed solution B is placed in an ultrasonic disperser and ultrasonically dispersed at a power of 250 to 300 W for 30 to 40 minutes to obtain a mixed solution C.
[0027] Furthermore, in step (4), the refrigeration temperature is maintained at 8 to 10 degrees Celsius.
[0028] Furthermore, in step (4), the refrigerated storage time does not exceed 7 days.
[0029] Furthermore, the dry materials of the concrete in step (6) include cement, fly ash, silica fume and quartz sand.
[0030] Furthermore, the mass ratio of concrete dry materials is:
[0031]
[0032] The method for pretreating and preserving graphene oxide proposed by the present invention is simple and the process is easy to control. The method can generate graphene oxide concrete with excellent and stable performance, and the graphene oxide concrete prepared by using the treated graphene oxide after being stored for 7 days can still maintain excellent material properties. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the embodiments, but it should not be understood that the above subject matter of the present invention is limited to the following embodiments. Without departing from the above technical ideas of the present invention, various substitutions and changes are made according to the common technical knowledge and customary means in the art, which should all be included in the protection scope of the present invention.
[0034] Embodiment 1:
[0035] The preparation method of high-strength graphene oxide concrete comprises the following steps:
[0036] (1) Use an electronic scale with an accuracy of 0.1 g to weigh 360 g to 450 g of water and 30 g to 38 g of water reducer in a 1000 ml beaker.
[0037] (2) Using an electronic scale with an accuracy of 0.01 g, weigh 16.0 g to 20.0 g of sodium dodecylbenzene sulfonate and 1.2 g to 1.5 g of gallic acid.
[0038] (3) Pour the sodium dodecylbenzene sulfonate and gallic acid weighed in (2) into the beaker containing water and water reducing agent in (1), stir with a glass rod until the solid is dissolved, and continue to stir evenly for 1 minute to obtain a mixed solution A.
[0039] (4) Using an electronic scale with an accuracy of 0.1 g, weigh 120 g to 150 g of a 0.01 wt% graphene oxide dispersion in a 1000 ml glass beaker, pour all of the mixed solution A into the weighed graphene oxide dispersion, and stir evenly with a glass rod for 1 to 2 minutes to obtain a mixed solution B.
[0040] (5) Place mixed solution B into an ultrasonic disperser and ultrasonically disperse mixed solution B at a power of 250 to 300 W for 30 to 40 minutes to obtain mixed solution C.
[0041] (6) Immediately pour the mixed solution C into a light-proof container and place it in a refrigerator adjusted to 8 to 10 degrees Celsius for storage. Maintain the temperature in the refrigerator at 8 to 10 degrees Celsius. The treated graphene oxide should not be stored for more than 7 days.
[0042] (7) Within half an hour before concrete mixing, weigh 200 g to 450 g of water and 8 g to 16 g of water reducer, and stir at a constant speed for one minute using a glass rod to prepare mixed solution D.
[0043] (8) Weigh cementitious materials and aggregates according to the mix ratio.
[0044] 3000g-4000g of cement, 600g-1000g of fly ash, 150g-250g of silica fume, and 5000g-6000g of sand. (9) Pour the materials weighed in (8) into a mixer and stir at a low speed for 30-60 seconds until the dry materials are evenly mixed.
[0045] (10) Add the mixed solution C and the mixed solution D to the dry material stirred uniformly in (10) at the same time, and the mixed solution C and the mixed solution D are not mixed before being added to the dry material.
[0046] (11) Stir the concrete until it is fully mixed and then pour it into the mold.
[0047] Embodiment 2:
[0048] This embodiment adopts the following mix ratio based on the technical solution disclosed in the invention content and embodiment 1: cement 750kg / m 3 , fly ash 155kg / m 3 , silica fume 35kg / m 3 , quartz sand 1180kg / m 3 , water 156.8kg / m 3 , water reducing agent 10kg / m 3 , 0.01wt% graphene oxide dispersion 28.2kg / m 3 , sodium dodecylbenzene sulfonate 3.76kg / m 3 , Gallic acid 282g / m 3 Among them, the quartz sand grading is shown in the following table.
[0049] Table 1 Quartz sand gradation
[0050] A graphene oxide processing method for preparing graphene oxide concrete-3-
[0051] Particle size Cumulative mass residue (%) 4.75mm 0 2.35mm 4 1.18mm 32 600μm 53 300μm 85 150μm 99
[0052] Embodiment 3:
[0053] This embodiment is tested based on the technical solution disclosed in the content of the invention and embodiment 1:
[0054] The preparation of material performance test specimens includes the following steps:
[0055] (1) Use an electronic scale with an accuracy of 0.1 g to weigh 402 g of water in a 1000 ml beaker, and then use a rubber dropper to drop 34 g of water reducing agent into the beaker.
[0056] (2) Using an electronic scale with an accuracy of 0.01 g, weigh 17.9 g of sodium dodecylbenzene sulfonate and 1.3 g of gallic acid.
[0057] (3) Pour the sodium dodecylbenzene sulfonate and gallic acid weighed in (2) into the beaker containing water and water reducing agent in (1), stir with a glass rod until the solid is dissolved, and continue to stir evenly for 1 minute to obtain a mixed solution A.
[0058] (4) Using an electronic scale with an accuracy of 0.1 g, 134 g of 0.01 wt% graphene oxide dispersion was weighed into a 1000 ml glass beaker, and the mixed solution A was poured into the weighed graphene oxide dispersion. The mixture was stirred evenly for 1 minute using a glass rod to obtain a mixed solution B.
[0059] (5) Mixed solution B was placed in an ultrasonic disperser and ultrasonically dispersed at a power of 260 W for 35 minutes to obtain mixed solution C.
[0060] (6) Immediately pour the mixed solution C into a 1000 ml white opaque plastic bottle and place it in a refrigerator adjusted to 8°C. Maintain the temperature in the refrigerator at 8-10°C.
[0061] (7) Repeat (1) to (6) to prepare and store two portions of mixed solution C, which are then stored for 7 days.
[0062] (8) Half an hour before mixing the concrete, weigh 688 g of water and 27 g of high-efficiency polycarboxylate water reducer, and stir them at a constant speed for one minute using a glass rod to prepare a mixed solution D.
[0063] (9) According to the mix ratio, weigh 7125g of cement, 1473g of fly ash, 332.5g of silica fume, and 11.21kg of sand. (10) Pour the cement, fly ash, silica fume, and sand into a mixer and stir at low speed for 60 seconds until the dry materials are evenly mixed.
[0064] (11) adding the mixed solution C and the mixed solution D to the dry material stirred in (10) at the same time, and the mixed solution C and the mixed solution D are not mixed before adding to the dry material;
[0065] (12) The concrete was stirred until fully uniform and poured into a 100 mm cubic mold to prepare a concrete compressive strength test piece.
[0066] After the graphene oxide concrete is prepared through the above steps, the material is immediately placed in a standard curing box for curing. The concrete curing conditions are a temperature of 20±1 degrees Celsius and a humidity of 95±2%. Referring to the above steps, specimens 1 to 5 are prepared, wherein:
[0067] When preparing sample 1: in step (4), graphene oxide was not added.
[0068] When preparing specimen 2: in step (5), the graphene oxide was not subjected to ultrasonic dispersion treatment, and the mixed solution B was used as the mixed solution C, and the graphene oxide concrete was immediately prepared after being stirred evenly.
[0069] When preparing specimen 3: the 7-day storage in step (7) was not performed, and graphene oxide concrete was prepared immediately.
[0070] When preparing specimen 4: step (6) was changed to preparing graphene oxide concrete after storing it in a light-proof environment at room temperature of 22±3 degrees Celsius for 7 days.
[0071] When preparing specimen 5: Step (6) is to prepare graphene oxide concrete after storing it in a light-proof environment at 8 to 10 degrees Celsius for 7 days.
[0072] Test results:
[0073] Nine specimens were prepared for each of the five specimens 1 to 5. Three specimens were taken from each specimen for standard compressive strength tests at 3 days, 7 days, and 28 days of curing. The test results are as follows:
[0074] Table 2 Compressive strength of graphene oxide concrete after 3 days of curing (MPa)
[0075] Test piece number (type) The first test piece The second test piece The third test piece average value Specimen 1 52.0 51.3 52.1 51.8 Specimen 2 53.3 54.8 51.3 53.1 Specimen 3 63.1 62.6 64.5 63.4 Specimen 4 47.8 47.2 46.5 47.2 Specimen 5 61.5 62.0 60.7 61.4
[0076] Table 3 Compressive strength of graphene oxide concrete after curing for 7 days (MPa)
[0077] Test piece number (type) The first test piece The second test piece The third test piece average value Specimen 1 62.7 62.2 65.2 63.4 Specimen 2 63.5 60.8 62.7 62.3 Specimen 3 74.3 76.9 78.6 76.6 Specimen 4 58.7 56.9 59.2 58.3 Specimen 5 74.9 74.0 72.8 73.9
[0078] Table 4 Compressive strength of graphene oxide concrete after 28 days of curing (MPa)
[0079] Test piece number (type) The first test piece The second test piece The third test piece average value Specimen 1 81.7 79.2 80.2 80.4 Specimen 2 83.5 79.8 81.9 81.7 Specimen 3 96.3 94.9 93.6 94.9 Specimen 4 72.0 73.3 77.0 74.1 Specimen 5 90.6 90.3 91.8 90.7
[0080] Test result analysis:
[0081] (1) The test results of specimens 1, 2, and 3 show that graphene oxide needs to be properly dispersed before being added to concrete. Undispersed graphene oxide has agglomeration phenomenon, which makes it unable to improve the compressive strength of concrete. After graphene oxide was added to concrete without ultrasonic dispersion, the compressive strength of graphene oxide concrete did not show significant strength improvement within 28 days. Specifically, at the ages of 3, 7, and 28 days, the compressive strength of concrete prepared with undispersed graphene oxide increased by 2.5%, -1.7%, and 1.6% respectively compared with ordinary concrete. Graphene oxide was added to concrete after ultrasonic dispersion, which significantly improved the compressive strength of concrete within 28 days. At the ages of 3, 7, and 28 days, the compressive strength of graphene oxide concrete increased by 22.4%, 20.8%, and 18.0% respectively compared with ordinary concrete.
[0082] (2) The test results of specimens 3, 4, and 5 show that after ultrasonic dispersion, graphene oxide should be stored using appropriate storage technology to ensure the dispersion degree of the material before use. The low-temperature storage technology proposed in the present invention is conducive to achieving the above purpose within a certain period of time. Graphene oxide that has been ultrasonically dispersed and stored at room temperature will show serious agglomeration after 7 days, and the performance of the material will change significantly. The compressive strength of concrete prepared using graphene oxide of the above specifications is significantly lower than that of concrete prepared before graphene oxide is stored. Tests have shown that graphene oxide that has been ultrasonically dispersed and stored at low temperature has no significant material performance changes within 7 days, and the graphene oxide concrete prepared using it has no significant compressive strength changes. The specific comparison results are that after graphene oxide is ultrasonically dispersed and stored at room temperature for 7 days, the compressive strength of the concrete is reduced by 25.6%, 23.9%, and 21.9% at the ages of 3, 7, and 28 days, respectively. Compared with concrete produced directly after ultrasonic dispersion of graphene oxide and stored at low temperature for 7 days, the compressive strength of concrete at the ages of 3, 7, and 28 days decreased by 3.2%, 3.5%, and 4.4%, respectively.
Claims
1. A graphene oxide processing method for preparing graphene oxide concrete, characterized in that: The following steps are involved: (1) preparing the water reducing agent: placing the water reducing agent and water in a reactor and mixing them; (2) placing sodium dodecylbenzene sulfonate and gallic acid in a reactor and stirring to obtain a mixed solution A; (3) mixing the graphene oxide dispersion with the mixed solution A, and stirring to obtain a mixed solution B; and ultrasonically dispersing the mixed solution B to obtain a mixed solution C; (4) Immediately pour the mixed solution C into a light-proof container and refrigerate; (5) Prepare a mixture of water and water reducing agent D before mixing concrete; (6) Pour the dry concrete into the mixer and stir at a low speed until the dry concrete is evenly mixed; (7) adding the mixed solution C and the mixed solution D to the dry material stirred in step (6) at the same time, and the mixed solution C and the mixed solution D are not mixed before being added to the dry material; (8) Stirring the mixed system of step (7) until it is fully stirred to obtain concrete for pouring.
2. A graphene oxide processing method for preparing graphene oxide concrete according to claim 1, characterized in that: The mass ratio of mixed liquid B is: The mass ratio of mixed liquid D is: 200 to 450 parts water Water reducing agent 8 to 16 parts In step (7), the prepared mixed solution C and mixed solution D are used in a ratio of 1:1; When mixed solution C and mixed solution D are added with dry materials to prepare concrete, the water-cement ratio of the concrete is 0.18 to 0.
21.
3. A graphene oxide processing method for preparing graphene oxide concrete according to claim 2, characterized in that: The mass ratio of the water reducing agent used in step (1) to the graphene oxide dispersion used in step (3) is 1:3-4. The mass ratio of water used in step (1) to the graphene oxide dispersion used in step (3) is 3 to 4:
1.
4. A graphene oxide processing method for preparing graphene oxide concrete according to claim 1 or 2, characterized in that: The solid content of the graphene oxide dispersion is 0.005wt% to 0.01wt%, the graphene oxide has a diameter of 1μm to 7μm, a carbon content of 50% to 56%, and an oxygen content of 42% to 48%.
5. A graphene oxide processing method for preparing graphene oxide concrete according to claim 1 or 2, characterized in that: In step (3), the mixed solution A is stirred evenly for 1 to 2 minutes to obtain a mixed solution B.
6. A graphene oxide processing method for preparing graphene oxide concrete according to claim 1 or 2, characterized in that: In step (3), the mixed solution B is placed in an ultrasonic disperser and ultrasonically dispersed at a power of 250 to 300 W for 30 to 40 minutes to obtain a mixed solution C.
7. A graphene oxide processing method for preparing graphene oxide concrete according to claim 1 or 2, characterized in that: In step (4), the refrigeration temperature is maintained at 8 to 10 degrees Celsius.
8. A graphene oxide processing method for preparing graphene oxide concrete according to claim 1 or 2, characterized in that: In step (4), the refrigerated storage time does not exceed 7 days.
9. The method for processing graphene oxide for preparing graphene oxide concrete according to claim 2, characterized in that: The dry materials of the concrete in step (6) include cement, fly ash, silica fume and quartz sand.
10. A graphene oxide processing method for preparing graphene oxide concrete according to claim 9, characterized in that: The mass ratio of dry concrete is:
Citation Information
Patent Citations
Oxidized graphene and graphene reinforced cement based composite material and preparation method thereof
CN103130436A